Nano Scale Mechanical Properties of Carbon Black Conductive Ink in Improving Efficiency for Electronics - Mohd Zamberi, Mahani (2019)
As many times conductive ink has been famous as it can be more economic for modern conductive tracks if compared to traditional method. To that the use of nanoparticle of non-metals with high electric conductivity brings new prospects of printing conductive pattern. Carbon conductive inks is one of the conductive material used today as its purpose is to improve circuit for printed electronics who e better than conventional inks beside its mechanical properties are closely related . to the microstructural development. A such this study was conducted to identify the effects of mechanical properties particularly hardness , young's modulus creep strength and resistivity by manually lay-up so-called doctor¬-blading technique the carbon nanoparticle conductive .ink layer with three different thicknesses which 0.05 mm (1 layer), 0.15 mm (3 layer) and 0.25 mm (5 layer) bonded onto the low-cost flexible printed substrate structures. Since the carbon conductive inks applied by laying on the flexible polyethylene terephthalate (PET) manually, the surface thickness and flatness of the conductive ink were nonuniform . Nanoindentation is vastly used to study the displacement of materials under specific loads which can be performed for small volume of materials, thin film, surface coatings and interfaces over the length scale of new nanometers. Nanoindentation test implementation with various functions is to characterise carbon conductive ink performance based on the measurement obtained from the three different thickness. Therefore, the study is executed by using Shimadzu Dynamic Ultra-micron Hardness Tester to measure hardness, Young's modulus and creep strength by employing indentation load, displacement, and contact stiffness data at indentation depths accordingly. A data analysis procedure has been developed to estimate the contact area on the samples of conductive inks bonded to a flexible substrate. The satisfactory result as expected shows good mechanical properties such the higher value obtained from Young's modulus and hardness due to lower indentation depths of samples involved. But opposite result obtained for creep shows slight increments on the time value of five second which leads to good result. Meanwhile four-point probe resistance test was employed to measure the resistivity of the carbon conductive inks on flexible substrates. The results measured showed the resistance of the thicker layer of carbon conductive ink sample had lower value which lead to better electrical conductivity rather than the thinner layer conductive ink.